Answer:
For functions, the two notations mean the exact same thing, but "f (x)" gives you more flexibility and more information. You used to say "y = 2x + 3; solve for y when x = –1". Now you say "f (x) = 2x + 3; find f (–1)" (pronounced as "f-of-x equals 2x plus three; find f-of-negative-one").
Step-by-step explanation:
For functions, the two notations mean the exact same thing, but "f (x)" gives you more flexibility and more information. You used to say "y = 2x + 3; solve for y when x = –1". Now you say "f (x) = 2x + 3; find f (–1)" (pronounced as "f-of-x equals 2x plus three; find f-of-negative-one").